Engineering macroscale cell alignment through coordinated toolpath design using support-assisted 3D bioprinting - Lee, Jia Min (2022)
Aligned cells provide direction-dependent mechanical properties that influence biological and mechanical function in native tissues. Alignment techniques such as casting and uniaxial stretching cannot fully replicate the complex fibre orientation of native tissue such as the heart. In this study, bioprinting is used to direct the orientation of cell alignment. A 0°-90° grid structure was printed to assess the robustness of the support-assisted bioprinting technique. The variation in the angles of the grid pattern is designed to mimic the differences in fibril orientation of native tissues, where angles of cell alignment vary across the different layers. Through bioprinting of a cell-hydrogel mixture, C2C12 cells displayed directed alignment along the longitudinal axis of printed struts. Cell alignment is induced through firstly establishing structurally stable constructs (i.e. distinct 0°-90° structures) and secondly, allowing cells to dynamically remodel the bioprinted construct. Herein reports a method of inducing a macroscale level of controlled cell alignment with angle variation. This was not achievable both in terms of methods (i.e. conventional alignment techniques such as stretching and electrical stimulation) and magnitude (i.e. hydrogel features with less than 100 µm features).